Laparoscopic Repair for Recurrent Bilateral Inguinal Bladder Hernia following Bilateral Transabdominal Preperitoneal Repair. (6th December 2018) - Umemura, Akira; Suto, Takayuki; Fujuwara, Hisataka; Nakamura, Seika; Nitta, Hiroyuki; Takahara, Takeshi; Hasegawa, Yasushi; Sasaki, Akira
Abstract : Introduction . Although a recurrent inguinal hernia is sometimes observed as a supravesical hernia, it is extremely rare to encounter a bilateral bladder sliding hernia recurrence. In this report, we describe an extremely rare case of a recurrent bilateral supravesical bladder hernia after bilateral transabdominal preperitoneal repair (B-TAPP). Case Presentation . A 69-year-old man visited our hospital with complaints of bilateral groin swelling and frequent voiding after B-TAPP. A plain CT revealed that the urinary bladder was herniating into the bilateral supravesical hernias. He underwent laparoscopic bilateral supravesical bladder hernia repair using a bladder takedown approach and median TAPP. Discussion . In Japan, the current mainstream method of hernioplasty is TAPP. However, an immature surgical technique and inadequate mesh placement may increase the risk of recurrent hernias. We successfully repaired this patient's recurrent bilateral supravesical bladder hernias laparoscopically. Conclusion . This rare condition (recurrent bilateral supravesical bladder hernias after B-TAPP) was successfully treated by using the bladder takedown approach and median TAPP. During surgical training and later in clinical practice, surgeons should master a surgical technique for this procedure in order to reduce recurrent hernias.